2011
DOI: 10.2139/ssrn.1492670
|View full text |Cite
|
Sign up to set email alerts
|

Competition and the Cost of Debt

Abstract: This paper empirically shows that the cost of bank debt is systematically higher for firms that operate in competitive product markets. Using various proxies for product market competition, and reductions of import tariff rates to capture exogenous changes to a firm's competitive environment, I find that competition has a significantly positive effect on the cost of bank debt. Moreover, the analysis reveals that the effect of competition is greater in industries in which small firms face financially strong riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
154
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(167 citation statements)
references
References 68 publications
10
154
1
2
Order By: Relevance
“…We define tax‐based competition as the strategic interactions and responses by firms to the tax choices and attributes of their competitors. Although tax‐based competition is not a unique form of competition, we argue that taxes can provide a channel that shapes competition, similar to how some firms' labor cost advantages affect the choices of rivals (Bernard et al ; Valta ; Flammer ). In our setting specifically, we focus on tax‐based competition pertaining to organizational form choice as a mechanism that affects how competitors' income is taxed.…”
Section: Introductionmentioning
confidence: 79%
“…We define tax‐based competition as the strategic interactions and responses by firms to the tax choices and attributes of their competitors. Although tax‐based competition is not a unique form of competition, we argue that taxes can provide a channel that shapes competition, similar to how some firms' labor cost advantages affect the choices of rivals (Bernard et al ; Valta ; Flammer ). In our setting specifically, we focus on tax‐based competition pertaining to organizational form choice as a mechanism that affects how competitors' income is taxed.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, a series of papers that use tariff cuts to instrument for import competition have found that they affect firms' capital budgeting decisions (Fresard (), Bloom, Draca, and Van Reenen (), Frésard and Valta ()) and capital structure (Valta (), Xu ()).…”
mentioning
confidence: 99%
“…Comprehensive surveys of exposure (Bartram and Bodnar, ) do not furnish any empirical evidence that firms’ financial constraints affect their exposure, although recent work indicates that exposure increases with aggregate credit constraints (Bergbrant and Hunter, ) and is higher for financially distressed firms (Starks and Wei, ). In addition, the empirical literature is also silent as to whether customs and foreign trade regulations affect exposure, although how foreign trade is regulated could influence the level of competition domestic firms face from foreign producers (Valta, ). We find that exposure is higher for firms that report that these regulations are an obstacle to their operations.…”
mentioning
confidence: 99%
“…The power of our tests is likely due to the fact that we use measures of competition that reflect the actual competition individual firms face and the fact that we have a measure of exposure that is gross of any hedging actions. A small body of work highlights the importance of competition for different aspects of firm operations including cash flows, stock returns (Gaspar and Massa, ; Hou and Robinson, ; Irvine and Pontiff, ; Hoberg and Phillips, ; Peress, ), trade credit (Fisman and Raturi, ), and the cost of capital (Valta, ). Considering the evidence that competition is a dominant determinant of exposure and given the magnitude of the potential impact of exchange rate changes on both domestic and foreign‐involved firms, our paper extends this work in an important new dimension .…”
mentioning
confidence: 99%